Note Related to the Memorandum of Mr. Powel on the Glaussius Case - Héderváry, Claire de (1960)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Claire de Héderváry A note to W. M. Jordan on the case of a Hungarian refugee, Mr. Glaussius, who was dissatisfied with the treatment he received from the Uruguayan government.